Affinity Precipitation Of Enzyme By Using Conjugated Ligand-Poly(Nipam) Polymer - Syaubari, Syaubari; M, Saari M; T.G, Chuah; G, Zulkafli; M, Ishak (Jurnal Sains dan Teknologi Reaksi, 2005)
In this paper, preparation of N-isopropylacrylamide of varying transfer chain lengths was synthesized. p-Aminobenzamidine (PABA) was chemically linked to the carboxyl groups of these polymers to obtain thermoprecipitating affinity polymers. The polymer to which PABA was linked through a carboxyl groups exhibited increase with polymer containing various PABA. Investigations on experiment showed that this enhancement in trypsin binding by the polymers was due to the p-aminobenzamidines to microenvironmental effects. Recovery and specific activity of the trypsin recovered increased with the low molecular weight of polymer.Keywords: Ligand, p-aminobenzamidine, trypsin, recovery, affinity precipitation